Penerapan 7 Kebiasaan Anak Indonesia Hebat Dalam Pembentukan Karakter Melalui Kemitraan Orang Tua Dan Guru - Khuroisin Nuriyah; Imron Arifin; Yudithia Dian Putra (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2026)
This research is motivated by the importance of character development from an early age and the need for synergy between home and school to support positive behavioral habits in children. This study aims to describe and analyze the implementation of the 7 Habits of Great Indonesian Children through a partnership between parents and teachers at RA Miftahul Huda Sukorejo–Pasuruan. A qualitative case study approach was used, involving the principal, teachers, and parents of students as research subjects. Data were obtained through observation, in-depth interviews, and documentation. They were then analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. Data validity was maintained through triangulation of sources and techniques to ensure data trustworthiness. The results indicate that the partnership between parents and teachers was fostered through the Daily Contact Book, WhatsApp Group, and Parenting Class, resulting in effective two-way communication. This creates a strong mesosystem between home and school, enabling the 7 Habits to be implemented harmoniously in both environments. Research findings demonstrate positive impacts in the form of improved moral behavior, social character, learning motivation, and emotional and spiritual development in children, coupled with integrated home and school habits. Therefore, early childhood character development will be optimal if home and school work synergistically, consistently, and mutually reinforcingly within an integrated educational ecosystem.